Compatibility of Measurement Results using a Rotating Device for Estimating Fetal Weight And The Johnson Toshack Method Newborn Weight - Sariestya Rismawati; Etin Rohmatin (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
The early detection of fetal size during pregnancy could be Estimated by fetal weight especially in the 3rd semester and became appropriate management guidance in pregnancy and labor. This study aims to compare the estimated fetal weight and the newborn weight between the Rotating device for estimating fetal weight (RDEFW) media and Johnson Toshack method in 2019 at Tasikmalaya primary health care neonatal essential and obstetric services.This research is comparative analytic with a crossectional method in Tasikmalaya primary health care neonatal essential and obstetric services from January until February 2019. The sample of this research was 34 labor women, with a purposive sampling technique. The data are univariate and bivariate which are analyzed by paired t-test, independent t-test, and diagnostics test.The results found that no significant differences between RDEFW media and the Johnson Toshack method in estimated fetal weight and the newborn weight, with p-value, alpha (0.380), its explain that two methods could be used for estimated newborn weight. The diagnostic result showed that RDEFW has curation about 82.4℅, 0.88% lower than the Johnson Toshack method (91.4%. Meanwhile, the Johnson Toshack is more accurate than RDEFW, but it still counting that RDEFW could be another alternative way for estimated newborn weight.